Development of adsorbent from sugarcane bagasse for the removal of pollutants from chrome tanning effluents - Sultana, Razia (Array, 2021)
The leather sector is the second-largest export earning sector in Bangladesh which contributes to huge employment generation and economic development. However, the current situation of this sector is not good enough for its lack of cleaner technologies and waste management systems. Tanneries are using an ample amount of harmful chemicals that may impose a huge negative impact on human health and the environment. Therefore, it is an emerging requirement for the removal of pollutants from effluents before discharging them to the environment. For this, the development of an adsorbent from agricultural waste is significant for removing pollutants from the tanning effluent and greening the environment. In this study, a low-cost adsorbent is developed and used to remove pollutants from the chrome tanning effluent. The developed adsorbent is prepared from sugarcane bagasse and activated by using NaOH. The study was performed at pH 4, with an adsorption time of 1 hour, and the adsorbent doses of 2.5 g/L. The findings revealed that a considerable amount of pollution was mitigated with the reduction in BOD (42.17%), COD (75.00%), Cr2O3 (41.91%), TSS (81.85%), and TDS (84.24%).